Kupas Tuntas Peraturan Pajak Terbaru PPh Pasal 21 - Yessica Amelia; Ruslaini Ruslaini; Rina Amelia; Nasutiah Nasutiah (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Tax is a mandatory contribution paid by taxpayers to the state. The PPh Article 21 e-seminar is one method to provide education and socialization to the public regarding taxes, especially PPh Article 21. Through this e-seminar, it is hoped that public understanding of tax regulations can increase, so that compliance in reporting and paying taxes also increases. However, there are several challenges in implementing the e-seminar, such as limited human resources, access to technology, and digital literacy in the community. However, e-seminar has the advantage of easy access, time flexibility, and the use of attractive technology. By overcoming various challenges and maximizing the advantages it has, e-seminar has the potential to be an effective method to increase public tax awareness and compliance.